Structural Design and Experimental Study of a Toothed Coupling for Urban Rail Trains - He Penghui; Li Fuqiang; He Shizhong; Tao Gongan; Cheng Xiangxun; Zhang Xiangru; Zhao Yukai (Jixie chuandong)
According to the needs of the urban rail train connection between the drive motor and gearbox, a toothed coupling for urban rail trains is designed. During the design process, the structure of the toothed coupling, gear geometry parameters, the sealing structure, theoretical calculation of tooth flank backlash, the space motion analysis and so on are studied. Through the establishment of a three-dimensional model of the toothed coupling and based on the calculation software of Ansys, a finite element analysis of three operating conditions of the toothed coupling and the calculation and analysis of gear strength using ZGCAD gear software are carried out, a prototype of toothed coupling is designed and manufactured, and the periodic cycle test of the prototype is carried out. The research results can provide reference for the design of toothed coupling in other fields.